Multiple Gestation as a Risk Factor for SARS-CoV-2-Associated Adverse Maternal Outcome: Data From the COVID-19 Related Obstetric and Neonatal Outcome Study (CRONOS) - Sourouni, Marina; Germeyer, Ariane; Feißt, Manuel; Balzer, Alexandra; Köster, Helen; Minte, Annemarie; Brüggmann, Dörthe; Kohll, Celine; Reinhardt, Kristin; Möginger, Michaela; Leonhardt, Anja; Banz-Jansen, Constanze; Bohlmann, Michael; Fröhlich, Christiane; Backes, Clara; Hager, Dietrich; Kaup, Lisa; Hollatz-Galuschki, Elsa; Engelbrecht, Charlotte; Markfeld-Erol, Filiz; Hagenbeck, Carsten; Schäffler, Hening; Winkler, Jennifer; Stubert, Johannes; Rathberger, Katharina; Lüber, Laura; Hertlein, Linda; Machill, Antonia; Richter, Manuela; Berghäuser, Martin; Weigel, Michael; Morgen, Mirjam; Horn, Nora; Jakubowski, Peter; Riebe, Bastian; Ramsauer, Babett; Sczesny, Robert; Schäfer-Graf, Ute Margaretha; Schrey, Susanne; Kehl, Sven; Lastinger, Julia; Seeger, Sven; Parchmann, Olaf; Iannaccone, Antonella; Rohne, Jens; Gattung, Luise; Morfeld, Christine A.; Abou-Dakn, Michael; Schmidt, Markus; Glöckner, Michaela; Jebens, Anja; Sondern, Kathleen Marie; Pecks, Ulrich; Schmitz, Ralf; Möllers, Mareike (Geburtshilfe und Frauenheilkunde, 2023)
Studies have shown that pregnant women with COVID-19 have a higher risk of intensive care unit admission and invasive mechanical ventilation support than non-pregnant women. Pregnancy-associated physiological changes in respiratory function may contribute to the elevated risk. Alteration in lung volumes and capacities are attributed to the mechanical impediment caused by the growing fetus. Multiple pregnancies may therefore compromise functional lung capacity earlier than singleton pregnancies and contribute to severe respiratory symptoms of COVID-19.A total of 5514 women with a symptomatic SARS-CoV-2 infection during pregnancy registered in the COVID-19 Related Obstetric and Neonatal Outcome Study were included. The COVID-19-related adverse maternal outcomes were compared in 165 multiple versus 5349 singleton pregnancies. Combined adverse maternal outcome was defined as presence of COVID-19-related hospitalization and/or pneumonia and/or oxygen administration and/or transfer to ICU and/or death. Multivariate logistic regression was used to estimate the odds ratios and 95% confidence intervals were calculated.The frequency of dyspnea, likelihood of developing dyspnea in a defined pregnancy week and duration of the symptomatic phase of the COVID-19 infection did not differ between the two groups. On average, COVID-19-related combined adverse outcome occurred earlier during pregnancy in women expecting more than one child than in singleton pregnancies. The overall incidence of singular and combined COVID-19-associated adverse maternal outcomes was not significantly different between groups. However, regression analysis revealed that multiple gestation, preconceptional BMI > 30 kg/m2 and gestational age correlated significantly with an increased risk of combined adverse maternal outcome. Conversely, maternal age and medically assisted reproduction were not significant risk factors for combined adverse maternal outcome.Our data show that multiple gestation alone is a risk factor for COVID-19-associated combined adverse maternal outcome. Moreover, severe courses of COVID-19 in women expecting more than one child are observed earlier in pregnancy than in singleton pregnancies.
Keywords: COVID-19; SARS-CoV-2 infection; multiple pregnancy; maternal outcome; CRONOS